Late Diagnosis of Progressive Pseudorheumatoid Dysplasia in an Adolescent Patient: A Case Report and Review of the Literature - Maria A Karalexi; Anna Papadopoulou; Olympia Papakonstantinou; Marina Mitrogiorgou; Grigorios Skarantavos; Vassiliki Papaevangelou; Erato Atsali (Galenos Yayinevi, 2021)
We present an adolescent girl with severe kyphoscoliosis and inability of walking due to progressive pseudorheumatoid dysplasia (PPD) who was initially misdiagnosed as juvenile idiopathic arthritis for 9 years. The lack of inflammatory joint involvement and inflammatory laboratory parameters, along with the characteristic radiological findings should raise suspicion for PPD.